Dislocation-θ′ (Al2Cu) interactions during creep deformation of an Al-Cu alloy. (August 2022) - Milligan, Brian; Ma, Dong; Allard, Lawrence; Clarke, Amy; Shyam, Amit
Abstract: While precipitate-dislocation interactions are well-understood for Al-Cu alloys in tension, creep behavior has seen far less study. New, thermally-stabilized Al-Cu alloys have θ′ (Al2 Cu) as strengthening precipitates that remain stable up to 300 °C (∼60% of the melting temperature) and higher, where creep becomes essential to the mechanical behavior. This investigation identifies the precipitate-dislocation interactions in such an Al-Cu alloy using in-situ neutron diffraction and scanning transmission electron microscopy. Significant load transfer to the θ′ precipitates occurs, which can be attributed to dislocation loops on the interfaces of θ′ and the Al matrix. Thus, Orowan looping is identified to be the primary activity for precipitate-dislocation interactions. As Orowan looping and load transfer are associated with significant strain hardening, these results explain the excellent creep resistance seen in this alloy, and provide insights into the design of precipitation strengthened alloys with superior creep performance. Graphical abstract: Image, graphical abstract